Effects of stand age and soil microbial communities on soil respiration throughout the growth cycle of poplar plantations in northeastern China - Liu, Xiangrong; Hou, Lingyu; Ding, Changjun; Su, Xiaohua; Zhang, Weixi; Pang, Zhongyi; Zhang, Yanlin; Sun, Qiwu (Frontiers in Microbiology, 2024)
Many studies have identified stand age and soil microbial communities as key factors influencing soil respiration (Rs). However, the effects of stand age and soil microbial communities on Rs throughout the growth cycle of poplar (Populus euramevicana cv.'I-214') plantations remain unclear. In this study, we adopted a spatial approach instead of a temporal one to investigate Rs and soil microbial communities in poplar plantations of 15 different ages (1-15 years old). The results showed that Rs exhibited clear seasonal dynamics, with the highest rates observed in the first year of stand age (1-year-old). As stand age increased, Rs showed a significant decreasing trend.We further identified r-selected microbial communities (copiotrophic species) as key biological factors influencing the decline in Rs with increasing stand age. Other abiotic factors, such as soil temperature (ST), pH, soil organic carbon (SOC), nitrate nitrogen (NO3 --N), and the C/N ratio of plant litter (Litter C/N), were also significantly correlated with Rs. Increased stand age promoted fungal community diversity but suppressed bacterial community diversity. Bacterial and fungal communities differed significantly in abundance, composition, and function, with the Litter C/N ratio being a key variable affected by microbial community changes. This study provides crucial empirical evidence on how stand age affects Rs, highlighting the connection between microbial community assemblages, their trophic strategies, and Rs over the growth cycle of poplar plantations.